Non-motor symptoms: Impulse control disorders and dopamine dysfunction in Parkinson's disease - Strafella, Antonio (Henry Stewart Talks, 2023)
Non-motor symptoms in PD, Behavioral complications in Parkinson's disease (PD), Neuroimaging, Dopaminergic abnormalities in PD, Receptor abnormalities and neural network changes in PD, Impulse control disorders in PD, Post-synaptic imaging in PD, Pathological Gambling (PG), Dopamine transporter (DAT), PD and abnormalities in the PFC, Apathy and depression in PD, Subthalamic nucleus deep brain stimulation